2022
DOI: 10.1111/jcpe.13619
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of periodontal wound healing/regeneration by recombinant human fibroblast growth factor‐2 combined with β‐tricalcium phosphate, carbonate apatite, or deproteinized bovine bone mineral in a canine one‐wall intra‐bony defect model

Abstract: Aim To evaluate periodontal wound healing/regeneration of one‐wall intra‐bony defects treated with recombinant human fibroblast growth factor‐2 (rhFGF‐2) and beta‐tricalcium phosphate (β‐TCP), carbonate apatite (CO3Ap), or deproteinized bovine bone mineral (DBBM) in dogs. Materials and Methods The stability of rhFGF‐2 adsorbed onto the bone substitutes was evaluated by Enzyme‐Linked Immunosorbent Assay (ELISA). One‐wall intra‐bony defects (5 × 5 × 5 mm) created in five adult male beagle dogs were treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…Previous studies have reported that in periodontal tissues, owing to carbonate and calcium ion effects, the use of CO 3 Ap resulted in enhanced promotion of osteoclast migration and osteoblast differentiation and more significant bone formation compared to deproteinized bovine bone mineral (DBBM) and β-TCP in canine three-wall intrabony defects [ 28 , 29 ]. These promising results are broadly consistent with the present findings showing mature osteogenesis and osteoclast recruitment around residual CO 3 Ap granules that exhibit higher osteoconductivity than β-TCP [ 18 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Previous studies have reported that in periodontal tissues, owing to carbonate and calcium ion effects, the use of CO 3 Ap resulted in enhanced promotion of osteoclast migration and osteoblast differentiation and more significant bone formation compared to deproteinized bovine bone mineral (DBBM) and β-TCP in canine three-wall intrabony defects [ 28 , 29 ]. These promising results are broadly consistent with the present findings showing mature osteogenesis and osteoclast recruitment around residual CO 3 Ap granules that exhibit higher osteoconductivity than β-TCP [ 18 ].…”
Section: Discussionsupporting
confidence: 93%
“…In the previous reports, Sato [ 17 ] and Shirakata [ 18 ] compared the regenerative ability of CO 3 Ap to that of DBBM. DBBM is composed of low-absorbable demineralized bovine bone and is recommended for its biocompatibility and new bone formation properties [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may explain the greater bone healing of 1–2-wall defects following the combination therapy used in the current study. Recently, Shirakata et al reported that DBBM seems to be a suitable carrier for rhFGF-2 and that rhFGF-2/DBBM treatment promotes favorable periodontal regeneration compared with rhFGF-2, rhFGF-2/β-TCP, and rhFGF-2/CO 3 Ap treatments in one-wall intra-bony defects [ 38 ]. These findings collectively suggest that DBBM may be an effective scaffold or carrier to be used with rhFGF-2.…”
Section: Discussionmentioning
confidence: 99%